A critical analysis of the employees' right to strike and repercussions for participating in an unprotected strike : inconsistency on selective re-employment - Mmakola, Thukwe Solly (My University, 2022)
The study will analyse the legal position of the right to strike and the consequences of participating in an unlawful strike. The study will provide a brief practical implication of employees dismissed for participation in an unlawful and/or unprotected strike and the employer’s right to reemploy any employee dismissed for a misconduct relating to unlawful and/or unprotected strike. The study will further make a brief comparison with the labour law position relating to strikes in the United Kingdom (“UK”). At the end provide recommendations on how the law on participation on unlawful and/or unprotected strikes and reemployed of employees dismissed on misconduct relating to participation in an unprotected strike can be developed and improved.
Thesis (LLM.) -- University of Limpopo, 2022
Keywords: Employee right to strike; Strike participation; Unprotected strike; Inconsistency of selective re-employment; Employee rights; Employees -- Dismissal of -- Law and legislation; Strikes and lockouts -- Law and legislation [150]; Employment re-entry